Belydenisuitsprake as Pauliniese briefoorgange - Roberts, J. H. (Hervormde teologiese studies, 1988)
Credal statements as Pauline epistoraly transitions In view of the fact that I have previously found five occurrances of credal statements in the Pauline literature, the function of which were to effect a transition from letter opening to letter body, the three cases of Romans 1: 16—17, Ephesians 1: 22—23, and Colossians 1: 13—20 were analysed with a view to their credal content and function towards the communication of these letters. The analyses were preceded by a discussion of recent research on credal material in the New Testament.